Contesting Catholicity: Theology for Other Baptists. Five Perspectives - V - Contesting Catholicity: Theology for Other Baptists. By Curtis W. Freeman. Waco, TX: Baylor University Press, 2014. xi + 466 pages. $49.95. - Medley, Mark S. (Horizons, 2015)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0360966915001036/resource/name/firstPage-S0360966915001036a.jpg